Cumulative Belief Degrees Approach for Assessment of Sustainable Development - Ünlüçay, Hazal; Ervural, Beyzanur Çayır; Ervural, Bilal; Kabak, Özgür (Springer International Publishing, 2016)
Over the past decades, sustainable development has emerged as one of the most prominent issues at all levels of society, from the global to the local level. To achieve a better balance between the economic, social and environmental dimensions of sustainable development in all countries of the world, starting from underdeveloped countries to developed countries, the right implementation of the sustainable development principles has a strategic significance that shapes the future of the countries. In this respect, measurement of sustainable development performance of countries is necessary in order to apply right sustainable development strategies, track the process, investigate the interactions between sustainability aspects, etc. The main purpose of this chapter is to demonstrate a new approach for measuring sustainable development levels of the countries using a cumulative belief degree approach. The approach enables the use of an incomplete data that is one of the critical problems in measuring sustainability of countries. Twenty-seven indicators for measuring 20 themes are selected based on the recommendations of United Nations Economic Commission for Europe (UNECE) and data availability. Finally, the proposed approach is applied to rank 138 countries according to their sustainable development performances based on the most recent data available.